Macromolecular Nanocrystal Structural Analysis with Electron and X-Rays: A Comparative Review - Khakurel, Krishna P; Angelov, Borislav; Andreasson, Jakob (Molecules (Basel, Switzerland), 2019)
Crystallography has long been the unrivaled method that can provide the atomistic structural models of macromolecules, using either X-rays or electrons as probes. The methodology has gone through several revolutionary periods, driven by the development of new sources, detectors, and other instrumentation. Novel sources of both X-ray and electrons are constantly emerging. The increase in brightness of these sources, complemented by the advanced detection techniques, has relaxed the traditionally strict need for large, high quality, crystals. Recent reports suggest high-quality diffraction datasets from crystals as small as a few hundreds of nanometers can be routinely obtained. This has resulted in the genesis of a new field of macromolecular nanocrystal crystallography. Here we will make a brief comparative review of this growing field focusing on the use of X-rays and electrons sources.
Keywords: Crystallography, X-Ray; molekulární struktura; rentgenové záření; Models, Molecular; molekulární modely; elektrony; nanocrystallography; Macromolecular Substances; nanočástice; electron diffraction; X-Rays; makromolekulární látky; Nanoparticles; X-ray free-electron laser; Electrons; Molecular Structure; krystalografie rentgenová